Experimental investigation on anisotropic permeability and its relationship with anisotropic thermal cracking of oil shale under high temperature and triaxial stress. (5th January 2019) - Wang, Guoying; Yang, Dong; Zhao, Yangsheng; Kang, Zhiqin; Zhao, Jing; Huang, Xudong
Highlights: Anisotropic permeability under high temperature and triaxial stress and anisotropic thermal cracking were investigated. Anisotropic thermal cracking was investigated by X-ray computed tomography over a broad range of temperatures. Correlation between anisotropic permeability and anisotropic thermal cracking was revealed. Abstract: A high-temperature triaxial permeability testing machine was used to study anisotropic permeability of oil shale at stresses that emulate in-situ conditions. The threshold temperature of permeability in the direction perpendicular to bedding is 450 °C and in the direction parallel to bedding is 400 °C. The magnitude of permeability of perpendicular bedding is low than 10 −20  m 2 below 450 °C, and increase from 10 −19 to 10 −17  m 2 at 450–600 °C. The magnitude of permeability of parallel bedding is 10 −19 to 10 −18  m 2 below 400 °C, and increase form 10 −16 to 10 −15  m 2 at 400 to 600 °C. The ratio of permeability of parallel bedding to permeability of perpendicular bedding was maximal at 450 °C. Simultaneously, sample microstructure was characterized by X-ray computed tomography. Thermal cracks mainly occur in the bedding direction, and cracks perpendicular to the bedding are rare. Thermal cracks caused by increased temperature are the main reason for the change of permeability in the direction parallel to bedding, and the connection of macropores is the main reason for the change of permeability in the direction perpendicular to bedding.